A quantitative analysis of cellular manufacturing in apparel industry by using simulation - Guoqiang Pan (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This research, by using the SIMIO simulation platform, provides a quantitative and comparative analysis of how the efficiency of four different cell production modes is affected. It is hoped that the results will be of some help for garment factories to optimize their production lines. Design/methodology/approach: The SIMIO simulation platform was employed in the research and comparisons were made of the simulation test results about the four popular cellular manufacturing modes. Findings: The operation mode, number of operators, and number of buffer areas are key factors affecting the production line efficiency, and need to be reasonably set to achieve the highest efficiency. Originality/value: As most research literature so far is qualitative, this research provided a simulation-based quantitative analysis of the production efficiency under different cell production modes.
Keywords: 650; cell production; SIMIO; simulation; apparel industry